ROLE OF PRIMARY SCHOOL TEACHERS IN TEACHING ENGLISH SUBJECT AT PUBLIC AND PRIVATE SCHOOLS OF SINDH, PAKISTAN - Zain ul abdin Rind; Dr. Arshad Saleem; Pari Pathan (International Journal of Contemporary Issues in Social Sciences, 2023)
The purpose of this study was to examine the role of primary school teachers in teaching English subject at government schools of Sindh. Descriptive research design was used to collect data from the students and approach was purely quantitative. In order to conduct the study, the data was collected from the students of primary schools who were in class four. The population of the study was district Matiari. The sample size was 100 students randomly and simple random sampling technique was used to collect the data from the students. Following data analysis, it became evident that Sindh government schools’ primary English instruction needed to be improved in the function of teachers. There was no statistical significance difference between male and female teachers at government primary schools. There was statistical significance difference between male and female teachers at private primary schools. Female teachers were more effective than male teachers at teaching English subject in grade 4 and 5. Additionally, private schools were good at teaching English subjects at primary level rather than public schools. The data indicated a need for targeted teacher training and professional development programs to enhance the proficiency of primary school teachers in delivering English language education, potentially leading to improved student outcomes in the subject.